A Three-Year Retrospective Analysis of Restorative Dental Treatment Patterns in a Nigerian Tertiary Hospital: Patient Demographics, Modalities, and Management Challenges - Edomwonyi, Augustine I; Afolabi, Jacob B; Aigbogun, Eric B; Edun, Olayinka T; Olaleye, Martins O (Update Dental College Journal, 2025)
Objective: To analyze and evaluate the patient management patterns for restorative treatment procedures at the Restorative Dentistry Clinic of a tertiary hospital in Nigeria over a three-year period, focusing on patient demographics, treatment modalities, and associated challenges to improve clinical outcomes and resource utilization. Materials and Methods: This study employed a retrospective design to analyze patient management patterns for restorative treatments at the Restorative Dentistry Clinic of the University of Medical Sciences Teaching Hospital, Ondo, Nigeria, from 2021 to 2023. Treatment records were reviewed, categorizing procedures as prosthodontics, endodontics, and operative dentistry. Data analysis utilized SPSS and other Microsoft software packages, with statistical significance set at p < 0.05. Results: A total of 316 restorative dental procedures were performed at the University of Medical Sciences Teaching Hospital, Ondo, between 2021 and 2023. Males comprised nearly half of the patients. The highest treatment volume occurred in 2022 (54.4%), followed by a significant decline in 2023 (19.3%). Prosthodontics led in treatment frequency (41.1%), with removable partial dentures being the most common procedure (73.8%) while fixed prosthodontics accounted for a small proportion (3.1%). Operative dentistry (38%) and endodontics (20.9%) followed. Notably, 25.6% of patients only consulted but did not undergo any treatment while 9.49% of the patient population cited financial constraints as a barrier. A statistically significant relationship was observed between financial constraints and the likelihood of not receiving treatment (p-value < 0.001), highlighting the impact of cost on patient care. Conclusion: This study revealed that age, gender, and socioeconomic factors influence restorative dental treatment needs. Younger patients predominantly sought care, while the elderly required more removable dentures. Treatment rates varied across departments, with Prosthodontics leading and Endodontics trailing. Financial constraints and material shortages significantly hindered treatment completion. Update Dent. Coll. j: 2025; 15(1): 20-24